Implementasi Model Pembelajaran ABCD5E Dalam Kelas Pengembangan National Character Cultivation Di PAUD Lab school UNNES - Eni Sulistyowati; R Agustinus Arum Eka Nugroho (Educatio, 2026)
This study aims to analyze the implementation of the ABCD5E learning model in the national character cultivation development class at PAUD Labschool Unnes which includes planning, implementation, and evaluation. In addition, to determine the supporting and inhibiting factors in the implementation of the ABCD5E learning model in the national character cultivation development class. The subjects in this study were the principal, class teachers, and students of the national character cultivation development class and GTK partners of the ABCD5E learning model. This study uses a qualitative method, through interview techniques, observation and documentation. Then the validity is carried out by triangulation of sources and techniques. The results of the study indicate that the implementation of the ABCD5E learning model at PAUD Labschool UNNES shows comprehensive results in creating a holistic, child-centered, and character development-oriented learning environment. The results of the study also show that there are several supporting and inhibiting factors, namely collaboration between teachers and parents in project planning, support from academics (UNNES PGPAUD lecturers) and the education office in curriculum validation, supporting APE, facilities and infrastructure and curriculum flexibility that allows teachers to innovate according to their competencies. While the inhibiting factor is the difficulty of teachers in observing children one by one during the learning process.